A Complete Concordance to the Greek Bible - Mazur, Roman (Eastern and Central European Voices. Supplements, 2023)
Intro -- Title Page -- Information about edition -- Preface -- Introduction -- Analytical Lexicon -- Complete Concordance -- Bibliography -- Users' instruction -- Verse numbering in the Septuagint and its parallel texts -- Abbreviations and symbols -- Analytical lexicon -- Complete concordance -- Α, α -- α -- Ααλ -- Ααρ -- Ἀβα -- Αββ -- Αβδ -- Αβε -- Αβι -- αβλ -- αβο -- ἅβρ -- ἄβυ -- Αβω -- Αγα -- Αγγ -- ἄγε -- ἄγη -- ἅγι -- αγκ -- Αγλ -- ἁγν -- ἄγξ -- αγό -- ἄγρ -- αγυ -- Αγχ -- ἄγω -- Αδα -- Αδδ -- ἄδε -- ᾅδῃ -- Αδι -- Αδλ -- Ἀδμ -- Αδν -- αδό -- Αδρ -- αδυ -- αδω -- αεὶ -- Αεμ -- αέν -- Αερ -- αετ -- Αζα -- Αζε -- Αζη -- Αζι -- Αζμ -- Αζο -- ἄζυ -- Αζω -- αηδ -- αὴρ -- Αθα -- Αθε -- Ἀθη -- Αθι -- ἆθλ -- αθο -- Ἀθρ -- αθυ -- αθῴ -- αἱ -- Αϊα -- αἶγ -- αιδ -- Αιε -- Αιζ -- αἰθ -- Αιι -- Αικ -- αιλ -- αἷμ -- αιν -- αἰξ -- αἰπ -- αἶρ -- αἷς -- Αιτ -- αἰφ -- Αιχ -- αἰὼ -- Ακα -- Ἁκε -- ακη -- ακι -- Ακκ -- ακλ -- ακμ -- ακο -- ἄκρ -- ακτ -- Ἀκύ -- Ακχ -- ακώ -- ἅλα -- αλγ -- ἁλε -- αλη -- ἁλὶ -- Αλκ -- αλλ -- ἅλμ -- αλό -- ἄλσ -- ἁλυ -- αλφ -- ἁλῷ -- ἅμα -- Αμβ -- αμέ -- Αμη -- αμί -- Αμμ -- αμν -- αμο -- ἄμπ -- Αμρ -- αμύ -- αμφ -- Αμω -- ἂν -- Ανα -- ἄνδ -- ανέ -- ανῇ -- ανθ -- Ανι -- Ανκ -- Ανν -- ανό -- αντ -- ἄνυ -- Ανω -- ἄξε -- ἄξι -- ἄξο -- ἄξω -- Αοζ -- αοί -- ἄοκ -- αορ -- Αου -- απ -- απά -- απέ -- απή -- απί -- ἄπλ -- ἄπν -- απὸ -- Ἀππ -- ἄπρ -- απτ -- ἄπυ -- Ἀπφ -- απω -- ἄρα -- Αρβ -- αργ -- ἄρδ -- Αρε -- ἄρῃ -- Αρθ -- Αρι -- αρκ -- ἅρμ -- Αρν -- ἄρξ -- Αρο -- ἁρπ -- αρρ -- Αρσ -- αρτ -- Αρφ -- Αρχ -- αρῶ -- ἃς -- Ασα -- Ασβ -- Ασγ -- Ασδ -- ασε -- Αση -- ασθ -- Ἀσί -- Ἀσκ -- ᾆσμ -- Ασν -- Ασο -- ασπ -- Ασρ -- Ασσ -- αστ -- Ασυ -- ασφ -- Ασχ -- ᾄσω -- Ατα -- ἅτε -- Ατη -- Ατθ -- Ατι -- ατμ -- ατό -- ἄτρ -- αττ -- ατυ -- Αυα -- αὐγ -- αὐθ -- Αυι -- αὐλ -- Αυν -- αὐξ -- αὔρ -- Αυσ -- αὐτ -- αὐτῷ -- αὐχ -- Αυω -- αφ -- αφα -- αφε -- ἁφή.